2021
DOI: 10.1371/journal.pntd.0009173
|View full text |Cite
|
Sign up to set email alerts
|

Host interactions of Aedes albopictus, an invasive vector of arboviruses, in Virginia, USA

Abstract: Background As an invasive mosquito species in the United States, Aedes albopictus is a potential vector of arboviruses including dengue, chikungunya, and Zika, and may also be involved in occasional transmission of other arboviruses such as West Nile, Saint Louis encephalitis, eastern equine encephalitis, and La Crosse viruses. Aedes albopictus feeds on a wide variety of vertebrate hosts, wild and domestic, as well as humans. Methodology/Principal findings In order to investigate blood feeding patterns of Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…8,11,13,15 Similarly, the fourth most common host, opossum, has been reported in five previous studies, also at lower levels, with the exception of Virginia. [9][10][11]14,16 Long Island Aedes albopictus fed less frequently on dogs compared with the representative proportion in numerous other studies. 8,10,11,[14][15][16][17] Notably absent from the Long Island blood meals were cows, deer, and birds, all of which were present on at least one site in our study and have been detected in at least six previous blood meal studies.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…8,11,13,15 Similarly, the fourth most common host, opossum, has been reported in five previous studies, also at lower levels, with the exception of Virginia. [9][10][11]14,16 Long Island Aedes albopictus fed less frequently on dogs compared with the representative proportion in numerous other studies. 8,10,11,[14][15][16][17] Notably absent from the Long Island blood meals were cows, deer, and birds, all of which were present on at least one site in our study and have been detected in at least six previous blood meal studies.…”
Section: Discussionmentioning
confidence: 69%
“…The proportion of human blood meals (32.2%) identified in Long Island was lower than reported in many other locations worldwide, 5,6,[12][13][14][15][16][17][19][20][21][22][23] but was higher than in some other studies from the United States (Hawaii, Missouri, North Carolina, Maryland, and Virginia). [7][8][9][10][11] More Ae. albopictus fed on cats in our study on Long Island than in any other location previously reported, with the exception of Virginia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations